Revolutionising health and social care: innovative solutions for a brighter tomorrow - a systematic review of the literature - Jennifer Kosiol; Tracey Silvester; Helen Cooper; Stewart Alford; Linda Fraser (BMC, 2024)
Abstract Background In an era marked by rapid technological advancements, changing demographics, and evolving healthcare needs, the landscape of health services has been undergoing a profound transformation. Innovation has emerged as a central force driving change in the healthcare sector, as stakeholders across the globe strive to enhance the quality, accessibility, and efficiency of healthcare services. Objective Within this dynamic context, this systematic literature review explored the barriers and driving forces behind successful health service innovation. Methods A comprehensive systematic literature review was conducted using the Griffith University Library search engine and databases that included PubMed, ProQuest, Web of Science, Scopus, and CINHAL. To achieve the study goal, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and the associated PRISMA checklist guided the review and reporting method. Results Findings from this review identified a need for a universal definition of health innovation that encompasses the unique complexities and challenges within this context. In our comprehensive analysis of healthcare innovation, we have uncovered pivotal findings that underscore the indispensable nature of a well-structured framework. Conclusions To succeed in fostering innovation within the health and social care sectors, it is imperative to establish an overarching organisational culture that meticulously addresses the following key components: team challenges; communication and collaboration; governance goals and authentic leadership, environmental engagement; and innovation endurance. Through systematic analysis of existing literature, this review offers a definition of health innovation, covering its conceptual foundations, determinants, and barriers, and provides a framework for creating an innovative culture.